How does fish metamorphosis affect aromatic amino acid metabolism? - Pinto, W. (2014)
Aromatic amino acids (AAs, phenylalanine and tyrosine) may be specifically required during fish metamorphosis, since they are the precursors of thyroid hormones which regulate this process. This project attempted to evaluate aromatic AA metabolism during the ontogenesis of fish species with a marked (Senegalese sole; Solea senegalensis) and a less accentuated metamorphosis (gilthead seabream; Sparus aurata). Fish were tube-fed with three l-[U-14C] AA solutions at pre-metamorphic, metamorphic and post-metamorphic stages of development: controlled AA mixture (Mix), phenylalanine (Phe) and tyrosine (Tyr). Results showed a preferential aromatic AA retention during the metamorphosis of Senegalese sole, rather than in gilthead seabream. Senegalese sole’s highly accentuated metamorphosis seems to increase aromatic AA physiological requirements, possibly for thyroid hormone production. Thus, Senegalese sole seems to be especially susceptible to dietary aromatic AA deficiencies during the metamorphosis period, and these findings may be important for physiologists, fish nutritionists and the flatfish aquaculture industry.